2021
DOI: 10.3390/mi12070730
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Soft Tooling Inserts for Injection Molding with Integrated Automated Slides

Abstract: The production of injection-molding prototypes, e.g., molded interconnect devices (MID) prototypes, can be costly and time-consuming due to the process-specific inability to replace durable steel tooling with quicker fabricated aluminum tooling. Instead, additively manufactured soft tooling is a solution for the production of small quantities and prototypes, but producing complex parts with, e.g., undercuts, is avoided due to the necessity of additional soft tooling components. The integration of automated sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…According to the results described above, the remarkable findings of this study have great practical value and show excellent potential for application in the precision investment casting industry [ 20 , 21 ]. The main contribution of this study is the proposal of a low-cost and highly efficient method to prevent coolant leakage during wax injection molding and 3D-printed conformally cooled injection molds.…”
Section: Resultsmentioning
confidence: 85%
“…According to the results described above, the remarkable findings of this study have great practical value and show excellent potential for application in the precision investment casting industry [ 20 , 21 ]. The main contribution of this study is the proposal of a low-cost and highly efficient method to prevent coolant leakage during wax injection molding and 3D-printed conformally cooled injection molds.…”
Section: Resultsmentioning
confidence: 85%
“…In general, the manufacture of turbine blade by the lost-wax casting is very common. The fabricated injection mold can be used for low-volume production of wax patterns in the IC industry [ 25 ]. It could be concluded that the findings of this study are very practical and provide the greatest application potential in the foundry because the mass production of a wax pattern is a key process in the IC industry.…”
Section: Resultsmentioning
confidence: 99%
“…To build up a new and optimized strategy for the manufacturing process, integrating between many factors is very essential. The paper [9,10] shows that these factors include material, production, process, and information with computer-aided design techniques. The new trends in the efforts of improving product quality focus on the design process for complex molding.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%